Assessing handlers for competence in animal-assisted interventions - Howie, Ann R., 1955- (New directions in the human-animal bond., 2021)
"Through practical, real-life examples, Assessing Handlers for Competence in Animal-Assisted Interventions provides guidance to any person working with animals in any setting. Facilities that have volunteers who work independently are in the greatest need of competent handlers, yet many of those facilities accept handlers with only proof of animal vaccinations. Other facilities accept an evaluation of the animal-handler team without knowing whether that evaluation relates to their facility or client dynamics. Both of these problems easily can be remedied with basic guidance. Howie brings more than thirty years of experience as an AAI provider, coordinator, and mental health therapist to bear on the topic of competence for animal handlers. In a friendly, easy-to-read style, she clearly explains the need for competencies while identifying broad categories currently in use. She then outlines training that addresses those competencies based on individual facility and client dynamics. She further describes one model for easily integrating competency assessment into an interview and provides a form for documenting the competency assessment. Additionally, Howie addresses how to deal with problems that can arise in program management"--